The role of social studies learning in fostering tolerance and multicultural awareness of elementary school students through the SDGs approach - Eka Putri Desyani, Ni Putu; Putu Yuni Widari, Gusti Ayu; Aprika Apsarendra Putra, I Putu; Susiani, Ketut (JPGI (Jurnal Penelitian Guru Indonesia), 2025)
The problem faced in learning in Elementary Schools is how to foster an attitude of tolerance and multicultural awareness amidst existing social diversity. Social Studies (IPS) learning can play a strategic role in overcoming these challenges. The main objective of this study is to examine the role of IPS learning in fostering an attitude of tolerance and multicultural awareness of elementary school students through the Sustainable Development Goals (SDGs) approach. This study uses a qualitative approach with a literature review research design. The subjects in this study include relevant literature sources such as journal articles, books, and documents that discuss Social Studies learning, multicultural education, and SDGs integration. The data collection method is carried out using documentation techniques, and data analysis uses content analysis to extract relevant information. The results of the study indicate that Social Studies learning that integrates SDGs can increase social awareness and strengthen students' attitudes of tolerance towards cultural, social, and religious diversity. The conclusion of this study indicates that Social Studies learning with the SDGs approach can form a generation that is more tolerant and cares about diversity. The implication of this study is the importance of integrating SDGs values into the social studies education curriculum to create inclusive students who are ready to face global challenges. <w:LsdException Locked="false" Priority="50" Name="Grid Tab